Фразеологічний фонд казкових повістей Всеволода Нестайка - Чернявська, Інна; Chernyavskaya, Inna (Східноєвропейський національний університет імені Лесі Українки, 2013)
У пропонованій статті автор робить спробу визначити якісну розмаїтість фразеологічних одиниць, ужитих у казкових повістях В. Нестайка, за їхньою генетичною природою й з’ясовує комунікативну значущість фразеологізмів у художніх творах зазначеного жанру, у зв’язку з чим характеризує їхні прагматичні функції.In the article the author makes an attempt to determine the variety of phraseological units used in V. Nestaiko’s fairy tales according to their genetic nature (Ukrainian phraseologisms, phraseological units borrowed from Latin and English, and traced from Russian). The author also tries to determine communicative significance of phraseologisms in the stories of the mentioned genre and describes their pragmatic functions such as emotional, expressive, evaluative, appellate, characterologic and function of laconization.
Phraseological Fund of V. Nestaiko’s Fairy Tales
Keywords: фразеологічна одиниця; казкова повість; генетична природа; комунікативна значущість; прагматична функція; phraseological unit; fairy tale; genetic nature; Ukrainian phraseologism; borrowed phraseological unit; traced phraseological unit; communicative significance; pragmatic function